Investigation of diabetic sensorimotor polyneuropathy through neurophysiology and nerve ultrasonography in Type 2 Diabetes Mellitus / Thaarani Arumugam - Thaarani, Arumugam (2016)
The present study explored the role of ultrasonography (US) and neurophysiology in characterizing type 2 diabetes patients according to their neuropathy severity as determined by the Toronto Clinical Scoring System (TCSS). This study also aimed to comprehensively determine the relationship between nerve US and nerve conduction study (NCS) parameters in diabetic patients. The second research question was to investigate if there are any imaging markers that could possibly differentiate diabetic patients with neurophysiological evidence of demyelination and true chronic inflammatory demyelinating polyneuropathy (CIDP) patients. The study subjects were 100 symptomatic distal symmetrical polyneuropathy (DSP) patients and 40 age-matched healthy controls. A subset of nine DSP patients with neurophysiological features of demyelination (D-DSP) and six true CIDP patients were also recruited. DSP severity was ascertained through TCSS where patients are grouped into mild (score 6-8), moderate (9-11) and severe (12-19). Nerve electrophysiology and ultrasound were performed on both lower limbs and the non-dominant upper limb in DSP subjects, and in both upper and lower limbs in true CIDP and D-DSP subjects. Nerves cross sectional area (CSA) recordings were taken at standard anatomical sites. A diagnosis of DSP and CIDP was made based on existing criteria. Statistical analyses were performed using SPSS version 22. Our findings revealed that sural nerve was inexcitable in 19.1% of mild, 40.0% of moderate and 69.0% of severe DSP groups. In contrast, CSAs were measureable in all nerves of DSP patients and were significantly larger compared to controls. Patients with severe DSP had significantly larger nerves in the ulnar, peroneal, tibial and sural, compared to mild DSP patients. By receiver operating characteristic analysis, the cut-off value for sural at 2 mm2 was a good discriminator with area under curve (AUC) of 0.88 between the presence and absence of DSP (sensitivity 0.90 ;specificity 0.74) but performed less well in discriminating between severity of DSP v (cut-off 2.75mm2; AUC 0.62; sensitivity 0.59; specificity 0.73). Significant correlations were demonstrated between TCSS, most neurophysiology parameters and nerve CSA of ulnar, peroneal, tibial and sural. Significant enlargement of nerves was also found in true CIDP patients compared to D-DSP patients at non-entrapment sites in the proximal regions of the upper extremities. This research found that nerve US in DSP revealed enlarged CSA and these changes worsen with increasing disease severity thus serving as a useful, reliable and practical diagnostic tool especially when neurophysiology is unrevealing. The present study also found nerve US aids in differentiation of true CIDP from D-DSP patients by differences in the nerve enlargement and electrophysiological profile between these two groups. This is important when managing these groups of patients as CIDP is treatable.